METHODOLOGY OF COMPARATIVE ANALYSIS OF THE SEMANTIC AND STRUCTURAL FEATURES OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Mashhura Safoqulova Nasrullayevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This study explores the methodology of comparative analysis of phraseological units in English and Uzbek languages, focusing on their semantic and structural features. Phraseological units are considered an essential part of linguistic systems as they reflect cultural identity, worldview, and cognitive patterns of different language communities. The research examines how meanings are constructed and transformed in fixed expressions, as well as how their internal structure differs or coincides across the two languages.The study highlights that English and Uzbek phraseological units demonstrate both universal and culture-specific characteristics. While some expressions share similar semantic equivalents, others differ significantly due to historical, cultural, and linguistic factors. Structural analysis reveals variations in word order, grammatical patterns, and morphological composition.